2020
DOI: 10.1111/ijfs.14474
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive compounds and antioxidant activity from harvest to edible ripeness of avocado cv. Hass (Persea americana) throughout the harvest seasons

Abstract: The influence of regular air cold storage (7°C and 85 AE 5% RH) followed by ripening at shelf-life conditions (19-21°C and 65 AE 5% RH), on bioactive compounds of Hass avocados was investigated. Results showed that the content of mannoheptulose and perseitol decreased significantly already during cold storage and ripening period. The fatty acid profile and contents of tocopherols (a-and b-tocopherol) and phytosterols (b-sitosterol, stigmasterol, campesterol) remained unchanged from day 0 to edible ripeness. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(62 citation statements)
references
References 44 publications
(58 reference statements)
6
45
4
Order By: Relevance
“…Our analysis revealed that TPC varied between 28.50 ± 1.92 (Fino de Jete) and 174.90 ± 11.69 (Chaffey) mg GAE per 100 g of PW, recording an average value equal to 75.18 ± 57.94 mg GAE per 100 g PW. The mean value is higher than those reported for the flesh of other tropical fruits with high commercial impact, including kiwi, papaya, mango and avocado [7,10,45,58]. Furthermore, the mean value for TPC in our fruits was 10-fold higher than for cherimoya fruits from Portugal [59], but 3-fold lower than those obtained for the flesh of fruits from Ecuador [60].…”
Section: Total Phenolic Contentcontrasting
confidence: 81%
“…Our analysis revealed that TPC varied between 28.50 ± 1.92 (Fino de Jete) and 174.90 ± 11.69 (Chaffey) mg GAE per 100 g of PW, recording an average value equal to 75.18 ± 57.94 mg GAE per 100 g PW. The mean value is higher than those reported for the flesh of other tropical fruits with high commercial impact, including kiwi, papaya, mango and avocado [7,10,45,58]. Furthermore, the mean value for TPC in our fruits was 10-fold higher than for cherimoya fruits from Portugal [59], but 3-fold lower than those obtained for the flesh of fruits from Ecuador [60].…”
Section: Total Phenolic Contentcontrasting
confidence: 81%
“…The quantification of polyphenols was performed using the method described by Campos et al [ 27 ], with some modifications. The chromatographic separation was performed on an Ultimate 3000 Ultra high-performance liquid chromatography (UHPLC) system (Thermo Scientific, Germany), connected to a Quantum Access Max triple quadrupole mass spectrometer equipped with a heated electrospray ionization (HESI-II) probe (Thermo Scientific, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Propionic acid, succinic acid, mannoheptulose, perseitol, glucose, pentadienoic acid decreased with storage, while alanine, valine, phenylalanine, norleucine, increased [25]. Furthermore, has been reported that regular air cold storage for up to 37 days followed by ripening at shelf-life conditions increased the phenolic compounds [26]. Those changes could be related to the GQ sensory perception of Hass avocado at the "ready to eat" ripening stage.…”
mentioning
confidence: 86%
“…Our hypothesis was that sensory quality descriptors and general quality could be affected by localities, harvest season and storage duration. Therefore, the aim of this work was to evaluate the effect of harvest index (19,22,26 and 30% DM) and storage duration (0, 3, 4 and 5 weeks) on Hass avocado (Persea americana Mill) sensory quality.…”
Section: Introductionmentioning
confidence: 99%